DAMPAK RATIFIKASI PROTOKOL KYOTO TERHADAP KEBIJAKAN PERUBAHAN IKLIM AUSTRALIA PADA PEMERINTAHAN PERDANA MENTERI KEVIN RUDD TAHUN 2008-2010 - Hesti Sita Komala; Maria Indira Aryani (Universitas Halu Oleo, 2022)
The issue of climate change has become a more serious problem, as it involves various aspects of life. Growing awareness of the issue then drives countries around the world, including Australia, to bring it to the table of international forums so the best solution can be agreed upon. This collective effort has resulted in the existence of the Kyoto protocol. This research aims to study the effects of the protocol's ratification, which led to its domestic implementation through a variety of policies by the Australian government. The study was conducted using the compliance theory, with the 3 indicators of output, outcomes, and impact, to see the capacity of the Australian government in complying with the international agreement. This research is organized in a qualitative explanatory method in order to understand the causes and effects of specific phenomena. The results show that the Australian government has established two domestic policies following the ratification of the Kyoto protocol, and has met the three indicators of compliance theory and experienced significant impacts on its environment and economy.